(3GdebGdI GdUdGMjI aj CMjGA GdUfGYI GdWHjIs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3Ef GdSjO UdGM GdOfjG hGdOjf CHG GdeXaQ jhSa Hf CjhH aMjf aQZ ef hLhg GdSjGSI hCMGWI CQLGA GdeedcI hQCi Cf GdfXQ ai UfGYI GdWH ef Cge GdCehQGdfGaYI s
(3BNQgG (B:s
(3hgPg gi GdCSHGH GdJi JbVi gPg GdUfGYI hEPG cGf Gdbhd ajgG gh GdZQV GdebUhO ef gPg GdQSGdI abO bdJ ajgG eG ajg caGjI adjcf gPG BNQgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3bhHdJ gPg GdfSNI hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs